Дослідження та розробка ефективних стратегій оптимізації веб-додатків на основі технології React - Загнойко, І. Ю. (ХНУРЕ, 2024)
This work addresses optimizing React web app performance by reducing unnecessary re-renders, optimizing data caching/loading, minimizing API requests, and decreasing bundle sizes. Key techniques like React.memo, useMemo, client-side caching, code splitting, and lazy loading are utilized. The proposed methods aim to decrease render times, improve responsiveness, reduce API requests, and accelerate load times for an enhanced user experience. Implementation leverages tools like Webpack, React Profiler, and Lighthouse. This comprehensive approach delivers more efficient, high-performing React apps.
Keywords: веб-додаток; React; API